Efficacy and safety of ACEI/ARB drug plus Yishenhuashi Granule: a Meta-analysis - Zhao Qing; Zhen Min; Yang Yu-feng; Wu Yi-lian; Shu Wei (Linchuang shenzangbing zazhi)
Objective To systematically evaluate the efficacy and safety of Yishenhuashi Granule plus ACEI/ARB drug for chronic glomerulonephritis（CGN）and provide evidence-based references for clinical practices.Methods Randomized control trials（CTs）and quasi-randomized control trials（qRCTS）related to treating CGN with Yishenhuashi Granule plus ACEI/ARB drug were collected from the databases of PubMed, Embase, Cochrane Library, CNKI,WangFang, VIP and CBM.The quality of included studies was evaluated and RewMAN 5.3 utilized for data analysis.Results Twenty eligible studies of 2885 cases were finally included.Meta-analysis indicated that Yishenhuashi Granule plus ACEI/ARB drug could improve clinical efficacy of CGN [OR=4.46,95%CI（3.45,5.76）] through reducing serum creatinine（Scr）（MD=-17.70,95%CI（-22.74,-12.66）,P<0.01）,urinary nitrogen（BUN）（MD=-1.67,95%CI（-1.89,-1.46）,P<0.01）,urinary protein quantification（24 hUTP）[MD=-0.41,95%CI（-0.45,-0.36）] and plasma albumin（Alb）[MD=2.34,95%CI（0.88,3.80）] without a greater incidence of adverse reactions.However, there was no obvious effect in lowering hematuria [MD=-1.71,95%CI（-4.38,0.86）,P=0.19].Conclusions As compared with ACEI/ARB drug alone, Yishenhuashi Granule plus ACEI/ARB drug can improve overall effective rate and restore renal function.And more clinical proofs are required for further validation due to limited quantity/quality of included studies.